2022
DOI: 10.3390/transplantology3020015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Porcine Precision-Cut Kidney Slices as a Model for Transplant-Related Ischemia-Reperfusion Injury

Abstract: Marginal donor kidneys are more likely to develop ischemia-reperfusion injury (IRI), resulting in inferior long-term outcomes. Perfusion techniques are used to attenuate IRI and improve graft quality. However, machine perfusion is still in its infancy, and more research is required for optimal conditions and potential repairing therapies. Experimental machine perfusion using porcine kidneys is a great way to investigate transplant-related IRI, but these experiments are costly and time-consuming. Therefore, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Since severe ischemia morphologically resembles autolysis, this could have distorted the findings and led to misclassification of some ischemic features as autolysis. Presence or absence of autolysis was not reported in a previous study on porcine precision-cut kidney slices (14), and autolysis could potentially be decreased with future improvements in the PCKS methodology. However, the feature of autolysis of this model could potentially serve as a starting point to study the rapid degradation of some cytoskeletal proteins reported in kidney transplants from donors with brain death compared with transplants from living donors (28).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Since severe ischemia morphologically resembles autolysis, this could have distorted the findings and led to misclassification of some ischemic features as autolysis. Presence or absence of autolysis was not reported in a previous study on porcine precision-cut kidney slices (14), and autolysis could potentially be decreased with future improvements in the PCKS methodology. However, the feature of autolysis of this model could potentially serve as a starting point to study the rapid degradation of some cytoskeletal proteins reported in kidney transplants from donors with brain death compared with transplants from living donors (28).…”
Section: Discussionmentioning
confidence: 82%
“…The presented study has several strengths. It is to our knowledge the first study to systematically compare a PCKS approach, an increasingly used methodology in kidney research (10)(11)(12)(13)(14), with a real disease model for kidney transplantation. We used in-depth morphological grading, allowing a detailed understanding of the morphological landscape throughout the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, experimental normothermic machine perfusion models are commonly used platforms for optimizing the resuscitation technique itself, and ex viv o renal function accurately reflects the condition of the kidney (Venema et al, 2019, 2021; Weissenbacher et al, 2019). In contrast to renal function, we were able to assess renal mitochondrial activity for an additional 48 h using the well‐established technique of precision‐cut kidney slices (Bigaeva, Stribos, et al, 2020; van Furth et al, 2022; Jensen et al, 2019; van Leeuwen et al, 2022; Stribos et al, 2016; Tingskov et al, 2021; Vaughan et al, 2022). Kidneys are well‐known consumers of oxygen to facilitate oxidative phosphorylation for the active reabsorption of sodium in the tubular cells (Balaban, 1990; Lassen et al, 1961; Singh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical structures and cell interactions of the lung are maintained. This technique has already proven its success in the fields of physiology, pharmacology, and toxicology [26][27][28]. In addition, mice have been accepted as a relatively accurate representation in the context of acute lung injury [26,29].…”
Section: Introductionmentioning
confidence: 99%